Cognitive Effects of Combined Amisulpride and Quetiapine Treatment in Patients With Refractory Schizophrenia: A Naturalistic, Prospective Study. (July 2020) - Molina, Juan de Dios; Quintero, Javier; García-Laredo, Eduardo; López-Muñoz, Francisco; Correas-Lauffer, Javier; Barbudo, Eduardo; Ceverino, Antonio; Mur, Carlos; Garcia-Resa, E.
Abstract : Background: Regarding the treatment of patients with resistant schizophrenia, different options exit, although they are supported by limited evidence. In this study, antipsychotic polypharmacy, comprising 1200 mg of amisulpride and 600 mg of quetiapine, was used. Clinical change evaluation was performed using neurocognitive evaluations. Study Question: The use of amisulpride and quetiapine will imply a clinical improvement in patients affected by schizophrenia, which will be specially reflected in a cognitive improvement. Study Design: Naturalistic and prospective study. Twenty-six patients were applied and assessed by a battery of neurocognitive evaluations since the pretreatment baseline until 6-month treatment. The patients had no biological response to medication, high social maladjustment, and a long clinical history of the disease. Kane and Brenner criteria for treatment-resistant schizophrenia were applied to choose the subjects. Measures and Outcomes: The cognitive improvement will imply a significant betterment, from the pretreatment baseline until 6-month treatment, in the following cognitive tests: Stroop Test, WAIS Coding Subtest, and Comprehensive Trail Making Test (CTMT). An improvement in the Calgary Depression Scale, Simpson–Angus Scale, and Visual Analogue Scale (EVA) will also be observed. This scales were been used during the baseline, 3 months after, and then, 6 months. Results: Subjects, after 6-month treatment with amisulpride and quetiapine, did show statistically significant differences in the assessed areas: WAIS Coding Subtest ( P < 0.001), CTMT A and B (CTMT A P < 0.034; CTMT B P < 0.000), and Stroop Tests: Word ( P < 0.001), Word-Color ( P < 0.007), and Interference ( P < 0.039). Furthermore, they showed a statistically significant difference in the Calgary Depression Scale ( P < 0.002), Simpson–Angus Scale ( P < 0.019), and EVA ( P < 0.001). Conclusions: The results of this report show a cognitive and clinical improvement in refractory patients after the administration of amisulpride and quetiapine.